Oral Fusobacterium nucleatum resists the acidic pH of the stomach due to membrane erucic acid synthesized via enoyl-CoA hydratase-related protein FnFabM - Xiaocong Li; Shipeng Zhang; Huafang Sheng; Yan Zhen; Buling Wu; Zhuang Li; Dingqiang Chen; Hongwei Zhou (Journal of Oral Microbiology)
Background and Objective Oral bacteria can translocate to the intestine, and their colonization efficiency is influenced by the gastrointestinal tract pH. Understanding how oral bacteria resist acidic environments is crucial for elucidating their role in gut health and disease.Methods To investigate the mechanisms of acid resistance in oral bacteria, an in vitro gastrointestinal tract Dynamic pH Model was established. This model was used to simulate the acidic conditions encountered by bacteria during their translocation from the mouth to the intestine.Results Fusobacterium nucleatum exhibited the highest survival rate in an acidified fluid mimicking the stomach pH (pH 1.5). The survival was significantly increased in the presence of erucic acid C22:1(n9) in cell membranes. Phylogenetic tree analysis revealed that C22:1(n9) synthesis was significantly associated with FnFabM gene expression in F. nucleatum at pH 1.5. Inhibition of FnFabM expression by cerulenin reduced the C22:1(n9) content and decreased the colonization efficiency of F. nucleatum in the stomach and jejunum of mice.Conclusions Oral F. nucleatum translocate to the intestine by resisting the acidic environment owing to the presence of erucic acid in its cell membrane, which is regulated by FnFabM. These results provide novel insights into the mechanisms underlying the oral bacteria survival in acidic environments and their potential to colonize the intestine; thus, shedding light on the oral-gut axis and its implications on human health.